A Systematic Review of the Debate and the Researchers of Disruptive Innovation - Carlos T. Kawamoto; Renata G. Spers (Journal of Technology Management & Innovation, 2019)
Despite the popularity of the term “disruptive innovation”, its applications have taken on different meanings. Clayton Christensen is a prominent author in the field but his approach has not been applied in a consistent manner. To elucidate the use of the term in business studies, this paper employs a bibliometric approach to provide a descriptive analysis of researchers and their relevant works in the network formed by the related literature, in addition to distinguishing and grouping associated authors. The results suggest a dissimilarity of objectives between two subgroups using the term “disruptive innovation”, and the discussion about Clayton Christensen’s specific meaning of the term seems to make sense to only one of them.